Paediatric Constipation;Think Beyond Thyroid Causes - Debnath, Ekta Malik; Datta, Rashmi Rasi; Debnath, Pinaki Ranjan; Jain, Anju (Journal of Nepal Paediatric Society, 2016)
Introduction: This study was designed to evaluate the importance of proper detailed history and examination of the patient as well as to determine the prevalence of unrecognized hypothyroidism among the paediatric patients with constipation attending the outpatient paediatric units in our hospital. Material and Methods: A retrospective review of medical records of paediatric patients ordered for thyroid function tests between July 2014 and June 2015 was performed. Total of 2210 paediatric patients were included in the study. A complete review of the medical records of these patients were performed which included indications for ordering thyroid tests, medical history, drug history, radiologic evaluation, other laboratory tests and subspeciality consultation.The samples were analyzed in the hormone unit of the Clinical Biochemistry Laboratory by a fully automated analyzer (Cobas e411, Roche). Data analysis was done using SPSS statistical software. Clinical diagnosis was made according to the paediatric reference ranges used in our clinical laboratory. Results: Out of all patients, 149 had history of constipation and 11 patients out of 149 had abnormal thyroid function. Repeat measurements after three months showed normal results for nine, while only two patients had results suggestive of hypothyroidism. Conclusion: Functional constipation is a condition which is to be diagnosed only by history or clinical examination. Thyroid profile where necessary is to be done after proper examination, to reduce the burden of cost to laboratory and society as well as exposing the pediatric patient to trauma. J Nepal Paediatr Soc 2016;36(2):143-146